THREE ELEMENTS STRUCTURE AND SOUND EXPECTATION CONCEPT IN SOUNDSCAPE -- A CASE STUDY OF THE NEW LAKESIDE PARK, HANG ZHOU - Ge Jiang; Guo Min; Hu Jun; Yue Miao (Lowland Technology International, 2012)
The three elements structure "sound, environment and human" is the core of soundscape. These three elements are closely related, influenced by each other. The specific meanings of the three elements, and how they interact, should be noted in soundscape studies. Only the three elements are considered together, can the findings obtained be convincing. In this paper, the three elements structure is made as a basis and the concept of sound expectation is put forward, which means: people will have a unique expectation on soundscape when they face a particular landscape. A set of research context is designed for sound expectation in order to apply this concept to actual projects. A Case Study of soundscape research in "New Lakeside Park" demonstrates the authenticity and feasibility of sound expectation concept.